2006
DOI: 10.1128/mcb.26.6.2347-2359.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nipped-A, the Tra1/TRRAP Subunit of the Drosophila SAGA and Tip60 Complexes, Has Multiple Roles in Notch Signaling during Wing Development

Abstract: The Notch receptor controls development by activating transcription of specific target genes in response to extracellular signals. The factors that control assembly of the Notch activator complex on target genes and its ability to activate transcription are not fully known. Here we show, through genetic and molecular analysis, that the Drosophila Nipped-A protein is required for activity of Notch and its coactivator protein, mastermind, during wing development. Nipped-A and mastermind also colocalize extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 53 publications
2
43
1
Order By: Relevance
“…Among the differentially expressed genes, Nipped-A transcripts were significantly upregulated in aged ISCs. The only previous study exploring the function of Nipped-A in Drosophila showed that it positively regulates N signaling in wing development (Gause et al, 2006). Interestingly, our findings do not support a role for Nipped-A in promoting N signaling in midgut ISCs as knocking down Nipped-A did not phenocopy the N loss-offunction phenotypes.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Among the differentially expressed genes, Nipped-A transcripts were significantly upregulated in aged ISCs. The only previous study exploring the function of Nipped-A in Drosophila showed that it positively regulates N signaling in wing development (Gause et al, 2006). Interestingly, our findings do not support a role for Nipped-A in promoting N signaling in midgut ISCs as knocking down Nipped-A did not phenocopy the N loss-offunction phenotypes.…”
Section: Discussioncontrasting
confidence: 53%
“…The function and biological importance of Drosophila Nipped-A is largely uncharacterized on a tissue-and cell-specific level. So far it has only been shown that Nipped-A promotes N signaling activity in wing development (Gause et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, loss of function mutations in trr1 gene of C. elegans cause developmental defect (Ceol and Horvitz, 2004). In addition, a genetic study in Drosophila showed that Nipped-A plays a role in Notch signaling and wing development (Gause et al, 2006). These studies provide evidence that TRRAP/Tra1/trr1/ Nipped-A plays an essential role in development, although its involvement in different pathways during embryogenesis remains to be elucidated.…”
Section: Essential Function Of Trrap In Embryonic Developmentmentioning
confidence: 88%
“…Here, the RAM domain of NICD allows its interaction with CSL, which facilitates the binding of MAM at the interface between the ANK domain of NICD and CSL (Choi et al, 2012). This complex further recruits coactivators, such as histone acetyltransferases (CBP/p300) and chromatin remodeling complexes, which mediate the transcription of Notch target genes (Wallberg et al, 2002;Kadam and Emerson, 2003;Gause et al, 2006). Kinases, such as glycogen synthase kinase 3b (GSK3b), granulocyte colony stimulating factor (G-CSF) and cyclin C/ cyclin-dependent kinase-8 (CDK8), have been shown to phosphorylate NICD, which is thought to be important for the stability of NICD and hence its activity (Inglés-Esteve et al, 2001;Espinosa et al, 2003;Fryer et al, 2004).…”
Section: Nuclear Events In Notch Signalingmentioning
confidence: 99%